KETERAMPILAN BERPIKIR KRITIS SISWA KELAS V PADA PEMBELAJARAN IPAS BERDASARKAN INDIKATOR BASIC SUPPORT, INFERENCE, DAN AD-VANCED CLARIFICATION: STUDI KUALITATIF DI SD NEGERI INPRES ANGKASAPURA JAYAPURA - Nurul Mutmainnah; Sri Wahyuni; Ernawati; Once Lina Asso (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the critical thinking skills of fifth-grade students in Natural and Social Sciences (IPAS) learning based on three indicators proposed by Ennis, namely basic support (building basic skills), inference (drawing conclusions), and advanced clarification (providing further explanation). This research employed a descriptive qualitative approach conducted at SD Negeri Inpres Angkasapura. Data were collected through tests, observations, interviews, and documentation. A critical thinking skills test was administered to 25 fifth grade students, after which three students were purposively selected as the main subjects, representing high, medium, and low ability categories. The data were analyzed through data reduction, data display, and conclusion drawing/verification. The results showed that students' critical thinking skills generally fell into the moderate category. On the basic support indicator, students were able to provide reasons and explain their answers with relevant arguments. On the inference indicator, students were reasonably able to formulate assumptions and draw conclusions based on the information obtained. Meanwhile, on the advanced clarification indicator, some students still experienced difficulties in developing reasoning and presenting arguments logically and systematically. These findings indicate that the ability to provide advanced explanations needs to be improved through IPAS learning that encourages critical thinking activities in a more systematic manner.